Screening and Diagnosis of Colorectal Cancer. (1988) - Irvine, E. Jan; Hunt, Richard H.
Abstract : Colorectal cancer is the second most common tumour in North American men and women. From present understanding of the pathogenesis and natural history of large bowel cancer, theoretically at least, the prevalence rate could be significantly decreased with careful application of simple screening measures and appropriately directed diagnostic tests. Until results of randomized controlled trials are available, it is important to recognize the pitfalls of mass screening or of substituting screening for proper investigative procedures. One possible approach co the diagnosis of colorectal cancer is outlined.